Lattice-Based Conditional Privacy-Preserving Authentication Protocol for the Vehicular Ad Hoc Network - Li, Quanrun; He, Debiao; Yang, Zhichao; Xie, Qi; Choo, Kim-Kwang Raymond (IEEE transactions on vehicular technology, 2022)
Vehicular ad hoc network (VANET) underpins most intelligent transportation systems and given the open nature of the wireless communication environment, edge nodes in the VANET are subject to varying levels of attacks. While there are a large number of conditional privacy-preserving authentication protocols in the literature, most of these protocols (whose security is guaranteed by classical cryptographic primitives) are not designed to resist quantum attacks. In this paper, we propose a lattice-based conditional privacy-preserving authentication protocol for VANETs, designed to simultaneously achieve mutual authentication and privacy protection. We also show that our protocol is secure in the random oracle model, relying on the small integer solution problem. Additionally, we demonstrate the potential utility of our protocol by evaluating its performance.